IMPLEMENTATION OF GROUP INVESTIGATION LEARNING MODEL TO IMPROVE INTEREST IN LEARNING AND UNDERSTANDING THE GEOGRAPHIC CONCEPT OF SMAN 1 SAMPANG STUDENTS - Dimas Bayu Putra (Journal Learning Geography, 2020)
The results of observations and interviews with students of class X IPS 2 , interest in learning geography before the application of the Group Investigation learning model of students is quite low. This is based on the statements of 20 students who expressed less interest in geography. Understanding the concepts of students of class X IPS 2 on geography learning material is still very low. data from the latest daily test results as many as 56% of students who scored below the average KKM (75). This study aims to (1) determine the increase in learning interest of students in class X IPS 2SMAN 1 Sampang on atmospheric dynamics material and its impact on life by applying the Group Investigation learning model (2) knowing an increase in understanding of the geography concept of class X IPS 2 students at SMAN 1 Sampang on atmospheric dynamics material and its impact on life by applying the Group Investigation learning model. This type of research is a class action ( classroom action research ) were conducted in two cycles, each cycle consisting of two meetings. This research subject graders X IPS 2 the second semester of the school year 201 9 /20 20 SMAN 1 Sampang. The results showed that (1) students' interest in learning after treatment experienced an increase in the overall indicator used, these indicators were: Feeling happy, student attention, student interest, and student learning involvement ; (2) students' understanding has increased from each cycle.Hasil pengamatan dan wawancara dengan siswa kelas X IPS 2, minat belajar geografi sebelum penerapan model pembelajaran Group Investigation siswa cukup rendah. Ini didasarkan pada pernyataan 20 siswa yang menyatakan kurang tertarik pada geografi. Memahami konsep siswa kelas X IPS 2 pada materi pembelajaran geografi masih sangat rendah. data dari hasil tes harian terbaru sebanyak 56% siswa yang mendapat skor di bawah rata-rata KKM (75). Penelitian ini bertujuan untuk (1) mengetahui peningkatan minat belajar siswa kelas X IPS 2 SMAN 1 Sampang pada materi dinamika atmosfer dan dampaknya terhadap kehidupan dengan menerapkan model pembelajaran Group Investigation (2) mengetahui peningkatan pemahaman konsep geografi. siswa kelas X IPS 2 di SMAN 1 Sampang pada materi dinamika atmosfer dan dampaknya terhadap kehidupan dengan menerapkan model pembelajaran Investigasi Kelompok. Jenis penelitian ini adalah tindakan kelas (class action research) yang dilakukan dalam dua siklus, setiap siklus terdiri dari dua pertemuan. Subjek penelitian ini adalah siswa kelas X IPS 2 semester 2 tahun pelajaran 201 9/20 20 SMAN 1 Sampang. Hasil penelitian menunjukkan bahwa (1) minat siswa dalam belajar setelah perawatan mengalami peningkatan dalam keseluruhan indikator yang digunakan, indikator ini adalah: Merasa bahagia, perhatian siswa, minat siswa, dan keterlibatan belajar siswa; (2) pemahaman siswa meningkat dari setiap siklus.